Fifty years of colic surgery. (12th March 2018) - Freeman, D. E.
Summary: Colic surgery is one of few treatments in which a veterinarian can use a skill to save an animal's life from a deadly disease within a short timeframe. Unfortunately, such success is not achieved without considerable risk for surgical failure, which is responsible for most complications in the immediate post‐operative period. The last 50 years have witnessed considerable improvements in colic surgery, although a ranking of the most important ones might not meet with universal agreement. Teamwork plays a critical role in the final outcome, starting and finishing with the referring veterinarian and owner. These individuals are responsible for promptly transferring the horse to a surgical facility and then dealing with aftercare and delayed complications. The surgeon is responsible for the intervening steps, including the decision on the need for surgery, and works with the anaesthesiologist to help a metabolically challenged patient to tolerate surgery and anaesthesia. Although early referral and improved diagnostic procedures can have a positive influence on survival, perceived improvements in surgery and anaesthesia need to be reviewed with some circumspection. Although more rigorous definitions and statistical analyses used in recent studies can invalidate comparisons with older studies, complication rates appear to be on the rise, despite putative improvements in dealing with them. This trend tends to diminish the value of colic surgery through increasing costs, overreliance on post‐operative pharmacological management, growing pessimism, high rates of intraoperative euthanasia, and possibly reduced long‐term survival. Future efforts should address these concerns, mostly through emphasis on prompt referral, good surgical technique and reducing the cost of colic surgery to an affordable level that saves more lives.